African Beliefs Concerning People with Disabilities: Implications for Theological Education - Ndlovu, Hebron L. (Journal of disability & religion, 2016)
This article describes the position and teachings of indigenous African beliefs concerning people with disabilities in contemporary African society. It examines explicit and implicit African attitudes and teachings pertaining to disability. The article also considers the implications of these African beliefs for theological education. Drawing largely on documented indigenous African beliefs from selected African cultures, and from Swaziland in particular, the contention of the article is that the position and teachings of indigenous African beliefs concerning people with disabilities is ambivalent: on one hand, some African beliefs promote the stigmatization and marginalization of people with disabilities through exclusion and depiction of them as objects of pity or ridicule, and as victims of evil forces; alternatively, other African beliefs inculcate positive and empathetic moral and ethical teaching aimed at protecting and empowering those living with disabilities by depicting them as full human beings who have the same rights, obligations, and responsibilities as "normal" persons.